Penerapan Data Mining Untuk Memprediksi Harga Cryptocurrency Ethereum Menggunakan Metode Backpropagation Neural Network - Yosef David Wibowo Susilo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The development of information technology at this time, especially developments in the field of digital finance, has made people switch from manual investment or storage to digital finance. Technological developments have also produced a new innovation, namely Cryptocurrency, or digital currency built on Blockchain technology. Due to the development of digital finance, many people are switching from conventional currencies to cryptocurrencies because of the promised benefits. Therefore, this study examines the use of the Backpropagation Neural Network to predict the price of cryptocurrency, namely Cryptocurrency Ethereum and finds out how effective the use of the Backpropagation Neural Network algorithm with 3 Backpropagation Neural Network architectures, namely 3-8-1, 3-9-1, and 3-10-1, the output of the Ethereum Cryptocurrency prediction results using the Backpropagation Neural Network algorithm in the form of a cryptocurrency prediction information system based on website.